Relationships between parenting style and sibling conflicts: A meta-analysis - Liu, Cong; Rahman, Mohd Nazri Abdul (Frontiers in Psychology, 2022)
Previous studies have shown that sibling conflicts are detrimental to physical and psychological development, as well as long-term human development. Although many studies have discovered relations between parenting style and sibling conflicts, these findings were contentious and did not provide a universal solution. Therefore, the meta-analysis was used as the method to determine the nature and magnitude of the relationships. There were a total of 14,356 participants in the 16 included studies, from which 55 effect sizes were extracted. According to the overall meta-analysis results, authoritative parenting (r = –0.201) did have the potential to reduce sibling conflicts. Neglectful (r = 0.389), inconsistent (r = 0.364), indulgent (r = 0.293), and authoritarian (r = 0.235) parenting styles were related to sibling conflicts in a positive way. Moreover, the study investigated the effectiveness of several moderator variables, such as children’s gender, age, region, outcome measure, and publication year. The research indicates that authoritative parenting is a protective factor of sibling conflicts. Moderator analyses found that gender, age, region, outcome measure, and publication year played moderating roles in the relationships. Finally, research limitations in the current study and expectations for future research, as well as theoretical contributions and implications for parenting practice, were presented. Systematic review registration [https://inplasy.com/inplasy-2022-8-0020/], identifier [INPLASY202280020].